English Vocabulary Size of Indonesian High School Graduates: Curriculum Expectation and Reality - Faisal Mustafa (IJELTAL (Indonesian Journal of English Language Teaching and Applied Linguistics), 2019)
Vocabulary is most important in learning a language, and thus it should be taught before teaching other language skills. Teachers need to plan which words to teach to make students learn vocabulary easier; however, Indonesian high school curriculum does not specify which vocabulary to teach. Therefore, this research was aimed at finding out the list of vocabulary required by the curriculum of junior and senior high schools in Indonesia and whether they have learned those words after graduating high school levels. Vocabulary used in texts in the national examinations is interpreted as the curriculum-expected vocabulary; therefore, the data for curriculum expectation were collected from previous national examinations. The vocabulary was classified based on most-frequently used vocabulary provided by Nation (2006) with 14,000 word-families categorized into 14 levels. Only the first 5 levels (1st - 5th 1,000) were used in this research. Later, 1,775 high school fresh graduates were tested with this vocabulary to predict the percentage of the vocabulary they have learned. The results showed that the expected vocabulary size of junior high school graduates was the 1st 2,000 words and the 1st 3,000 words for senior high school graduates. Compared to the graduate predicted vocabulary size, they only had 72% vocabulary in the 1st 1,000, 54% in the 2nd 1,000, 49% in the 3rd. These results suggest that the graduate vocabulary size has not satisfied the curriculum expectation; therefore, Indonesian high school students should be taught all words in the first 3,000 list to be able to comprehend texts in the national examination.